Melampaui Reduksi Ekonomistik: Rekonstruksi Teologi-Makna dalam Proyek Masyarakat Tanpa Kemiskinan Berbasis Psikologi Eksistensial - Ilman Rizqi Nuriyanto Suwarno; Dini Hanifah; Ali Hasan Siswanto; Astiana Leli Agustina; Verlina Dwi Maulani (Sujud: Jurnal Agama, Sosial dan Budaya, 2026)
The persistence of poverty amidst the advancement of modernity demonstrates the limitations of the dominant approach, which tends to reduce poverty to a purely economic issue. This approach ignores the dimensions of meaning, spirituality, and human existential awareness, thus failing to address the deepest roots of poverty reproduction. The research gap lies in the minimal integration of Islamic theology, Sufism, and existential psychology in building a more holistic alternative paradigm. This article aims to reconstruct the concept of a society without poverty through a theology-meaning approach based on humanistic-existential psychology, specifically Viktor Frankl's logotherapy. This research uses a conceptual qualitative method with an interdisciplinary approach that combines theological, philosophical, and psychological analysis. The analysis technique is carried out through a critical reading of classical and contemporary literature and a conceptual synthesis to formulate a new theoretical model. The main argument of this article asserts that poverty is not only a material crisis, but also a crisis of meaning (existential vacuum) that reinforces the cycle of individual and collective powerlessness. Therefore, efforts to create a society without poverty must involve a transformation of meaning through the reconstruction of theology as an emancipatory force and the integration of existential awareness into social structures. This article's scholarly contribution lies in the development of a meaning-based social transformation paradigm and the introduction of the concept of redistribution of meaning as a complement to economic redistribution in poverty studies. This approach offers a new direction in interdisciplinary research that connects theology, Sufism, and psychology within the framework of sustainable social transformation.